أثر الحركات في ترجمة آيات من القرآن الكريم الى الإنكليزية - ياسر يونس عبد الواحد (University of Mosul-college of Basic Education, 2012)
This research investigates the impact of inflections on translating some Qur'ānic verses into English. It attempts to show how translators deal with the verses in which inflection plays a big role in altering the verse meaning, and then, based on the accredited Qur'ānic interpretations, correcting the translations of the verses concerned. The research hypothesizes that the issue of inflection has not been given attention on the part of the translators of the Glorious Qur'ān, causing translation mistakes. From analyzing five translations of the Glorious Qur'ān, it has been found that the translators produced inaccurate translations as far as the issue of inflection is concerned. In order to achieve better understanding on the part of the TL reader, revising these translations is recommended.